Book of the Disappeared The Quest for Transnational Justice - Heath, Jennifer; Zahedi, Ashraf (Ethnic Conflict: Studies in Nationality, Race, and Culture, 2023)
Book of the Disappeared confronts worldwide human rights violations of enforced disappearance and genocide and explores the global quest for justice with forceful, outstanding contributions by respected scholars, expert practitioners, and provocative contemporary artists. This profoundly humane book spotlights our historic inhumanity while offering insights for survival and transformation.